2011
DOI: 10.1038/ncomms1199
|View full text |Cite
|
Sign up to set email alerts
|

A C2 domain protein kinase initiates phagocytosis in the protozoan parasite Entamoeba histolytica

Abstract: Phagocytosis is a process whereby particles are taken in by cells through mechanisms super ficially similar to those for endocytosis. It serves a wide range of functions, from providing nutrition in unicellular organisms to initiation of both innate and adaptive immunity in vertebrates. In the protozoan parasite Entamoeba histolytica, it has an essential role in survival and pathogenesis. In this study, we show that EhC2PK, a C2 domain containing protein kinase, and the Ca 2 + and actin binding protein, EhCaBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 38 publications
6
97
0
Order By: Relevance
“…Our results strongly suggest a regulatory role of this region in kinase activity of EhC2PK. It is clear from our previous studies that EhC2PK is involved in the initiation of erythrophagocytosis in E. histolytica (6). The requirement of a functional kinase domain was evident when it was observed that overexpression of the kinase-dead mutant and the C2 domain alone led to impaired phagocytosis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Our results strongly suggest a regulatory role of this region in kinase activity of EhC2PK. It is clear from our previous studies that EhC2PK is involved in the initiation of erythrophagocytosis in E. histolytica (6). The requirement of a functional kinase domain was evident when it was observed that overexpression of the kinase-dead mutant and the C2 domain alone led to impaired phagocytosis.…”
Section: Discussionmentioning
confidence: 89%
“…A few of the C2 domain containing PKCs have been shown to be involved in phagocytosis and regulation of actin polymerization (8,9). Our earlier observations have clearly indicated that the C2 domain of EhC2PK is necessary and sufficient to bind plasma membrane in the presence of Ca 2ϩ (6,10). Therefore, it is likely to provide an anchor for the formation of phagocytic machinery.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…63 Trogocytosis shares similarities to Eh phagocytosis of cells including EhC2PK, a C2 domain containing protein kinase that initiates the phagocytic cup and actin recruitment. 64 Not surprisingly, interference with the cytoskeletal and microfilament network within Eh also inhibited trogocytosis. Host cells that were nibbled on also experienced irreversible intracellular calcium increases (Fig.…”
Section: Invasion Into and Beyond The Epithelial Barriermentioning
confidence: 99%